(untitled) (Research, Society and Development, 2020)
The objective of the essay, through a qualitative and quantitative explanatory research, is to perform tests with the Autodesk Revit ® computer program, based on BIM technology, using Autodesk ® Insight360 and Green Building Studio tool to of a real model, with the thermal properties of the materials, generate the thermo-energetic simulation of a building that uses Pinus elliottii Glued Laminated Wood (MLC) as a structural element of beams and roof, seeing the material as a high potential product for constructive elements beyond sustainability by applying it. The analyzes of energy efficiency and material behavior were performed so that it was found that the results obtained together with the materials used in construction, especially the MLC, are adequate for the comfort parameters established by the standards and making it allied to construction precepts and bioclimatic architecture.